Pengaruh Penerapan Model Problem Based Learning Terhadap Hasil Belajar Tema 8 Subtema 1 - Hilda Farhatu Tajkiyah; Sumardi Sumardi; Santa Santa (STKIP Andi Matappa Pangkep, 2022)
This study aims to determine the effect of the Problem Based Learning model on learning outcomes for the environmental sub-theme where I live at Rancabungur 01 State Elementary School, Bogor Regency Class IV, especially in Thematic learning. This type of research is a type of quantitative research, the type used is quasi-experimental research with a nonequivalent control group design. The population in this study were all fourth grade students at SD Negeri Rancabungur 01 for the academic year 2021/2022 totaling 75 students who were also the research sample. Based on data analysis, there is a difference between the average pretest and posttest learning outcomes. Based on the calculation tcount of 5.234 is greater than the ttable of 1.99495. Because tcount tcount (5.234) > ttable (1.99495) then Ho is rejected. In addition, the pre-test learning outcomes obtained an average of 50. Meanwhile, the posttest learning outcomes obtained an average of 71. It can be stated that the Problem Based Learning model has an influence on the learning outcomes of the environment sub-theme where I live in class IV at SDN Rancabungur 01, Bogor Regency.